1977
DOI: 10.1113/jphysiol.1977.sp011838
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐electrode measurement of the intracellular pH and buffering power of mouse soleus muscle fibres.

Abstract: SUMMARY1. The intracellular pH (pHi) of surface fibres of the mouse soleus muscle has been measured in vitro using recessed-tip pH-sensitive microelectrodes.2. In 5 % CO2 and pH 7 40, the mean pH1 was 7 07 + 0 007 (s.E. of mean) at 370 C and 7-23 + 0.01 at 280 C. The difference between these two values is the same as the change in neutral pH between 37 and 280 C.3. Alteration of the CO2 level at constant external pH caused a biphasic change in pH1 with a rapid displacement followed by a slower partial recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

1983
1983
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 177 publications
(1 citation statement)
references
References 29 publications
0
0
1
Order By: Relevance
“…Hagberg et al (1983) [99] measured in vivo the pH i of rabbit skeletal muscle fibers using the double-barreled pH microelectrode. The pH i of 7.00 ± 0.09 found in this study was lower than that found in mouse soleus fibers in vitro using pH-sensitive microelectrodes (7.07) [100] or in rat soleus using double-barreled electrodes (7.1-7.2) [98]. They assumed that the higher bath pH and the lower level of CO 2 in those studies could explain this small discrepancy.…”
Section: Ph Microelectrodescontrasting
confidence: 74%
“…Hagberg et al (1983) [99] measured in vivo the pH i of rabbit skeletal muscle fibers using the double-barreled pH microelectrode. The pH i of 7.00 ± 0.09 found in this study was lower than that found in mouse soleus fibers in vitro using pH-sensitive microelectrodes (7.07) [100] or in rat soleus using double-barreled electrodes (7.1-7.2) [98]. They assumed that the higher bath pH and the lower level of CO 2 in those studies could explain this small discrepancy.…”
Section: Ph Microelectrodescontrasting
confidence: 74%